Indian women dentists perspectives towards balancing professional, personal and social responsibilities - Yeluripati Sai Nirupama; Naveen Kumar Boppana; Narayana Rao Vinnakota; Ravi Kumar Thetakala; Praneetha Kallakuri; Burri Kiran Karthik (Wolters Kluwer Medknow Publications, 2020)
Introduction: The literature on women in dentistry clearly shows the evolution and elevation of women in academic as well as clinical dentistry. Female dentists in India continue to face the need to balance their careers with the competing social and personal responsibilities of marriage, homemaking, and child rearing. Aim: To assess Indian Women Dentists perspectives towards balancing professional, personal, and social responsibilities. Methodology: This cross-sectional study was conducted for 1 month among 159 female dental professionals comprising all the female dental practitioners in Rajahmundry city and all the female interns, postgraduates, and academicians from 2 dental institutions in Rajahmundry city. A 23-item pretested questionnaire was distributed to the participants on the first day and collected after 1 day. The results were analyzed using SPSS software (V.22). The categorical data were analyzed using the χ2 test and P ≤ 0.05 was considered as statistically significant. Results: Among the study participants, 79.2% of study participants agreed that family commitments were not obstacles for their career (P = 0.02), 86.2% responded that women should be successful in both home-making and career and 89.9% of participants reported as not regretting being women and this finding was found to be statistically significant. Conclusion: Majority of the women perceived that women ought to balance professional, personal, and social responsibilities equally.